The current profile and situation of Iloilo provincial media practitioners in AM Radio stations. - Avelino, Sharon Faith
This study aims to know the current profile and situation of Iloilo provincial media practitioners in AM radio stations. This aims presents the profile of the media practitioners in the radio stations specifically in Bombo Radyo (DYFM), Radyo ng Bayan (DYLL), aksyon Radyo (DYOK), Super Radyo (DYSI) and IBC (DYBQ). The instruments used by the researchers in conducting this study were open-ended questionnaire and interview. A census of all media practioners in the said five radio stations were taken as respondents. This was conducted during the first semester of AY 2004-2005. Results show that the broadcasting profession in Iloilo AM radio stations is a viable profession in terms of improving the total way of life of broadcasters.